2019
DOI: 10.13181/mji.v28i3.2589
|View full text |Cite
|
Sign up to set email alerts
|

A recent update of the diagnostic methods for tuberculosis and their applicability in Indonesia: a narrative review

Abstract: Tuberculosis (TB) is a major global problem, especially with the high prevalence of HIV-TB co-infection. Delayed diagnosis and continual transmission contribute to high mortality in Indonesia, which has the third highest incidence of TB in the world, after China and India. Therefore, early diagnosis is needed to reduce the number of cases and to administer therapy to prevent the transmission of bacteria. The diagnosis of TB remains a challenge in clinical practice due to poor sensitivity and the requirement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
0
12
0
7
Order By: Relevance
“…This will have an impact on a lower immune system and greater exposure factors. 7,8 Several studies have shown that the most common additional symptom in TB patients is cough. This can be caused by infection with bacteria Mycobacterium tuberculosis in the lung parenchyma, irritating the…”
Section: Discussionmentioning
confidence: 99%
“…This will have an impact on a lower immune system and greater exposure factors. 7,8 Several studies have shown that the most common additional symptom in TB patients is cough. This can be caused by infection with bacteria Mycobacterium tuberculosis in the lung parenchyma, irritating the…”
Section: Discussionmentioning
confidence: 99%
“…As a type of GUTB, diagnosis of this disease are challenging, as signs and symptoms, such as LUTS and hematuria, may mimic other disorders, such as urinary tract infection, benign prostate hyperplasia, and prostate cancer. Most of the time, diagnosis of prostate TB are incidental, for example made by the pathologist while performing examination of prostate tissue specimen taken from biopsy or prostate resection 1,2,4 . TB in the male genitalia is commonly found in the prostate or epididymal.…”
Section: Discussionmentioning
confidence: 99%
“…Pemeriksaan XpertMTB/ RIF di Indonesia saat ini cenderung terpusat di daerah-daerah perkotaan. 20,21 Oleh karena itu, adalah sebuah tantangan untuk para klinisi terutama di daerah rural dalam menyingkirkan diagnosis TB dalam proses menegakkan diagnosis COVID-19.…”
Section: Diskusiunclassified